Presenteeism in Organizations: A Research on the Impact of Psychological Ownership in Healtcare Professionals - UYSAL, H.Tezcan; Ak, Murat; Yılmaz Kılıçkaya, Fatma (International Journal of Contemporary Economics and Administrative Sciences, 2024)
The purpose of this research is to examine the behaviors of presenteeism (PT) in employees and to determine whether psychological ownership (PO) has an effect on these behaviors. Accordingly, data has been obtained from 485 healthcare professionals in the public and private sectors by survey method and independent sample T Test and One-Way ANOVA Tests have been carried out with validity, reliability, normality, correlation, multiple regression analyses for this data. As a result of the analyses carried out; a negatively significant relationship has been found between PO and PT and a 1-unit increase in PO has been found to cause a decrease of 0.410 units on PT. However, it has been concluded that the level of PT in single employees is higher than that of married employees, PT is higher in private sector workers than in public sector workers, and in employees under 21, compared to those aged 21-40 and 41-60, and as the duration of work experience and monthly income level increases, PT decreases gradually.